Investigation on thickness and annealing effects on physical properties and electrical circuit model of CuO sprayed thin films. (June 2020) - Ben Saâd, Haifa; Ajili, Mejda; Dabbabi, Samar; Kamoun, Najoua Turki
Abstract: In this current work, copper oxide thin films (CuO) were deposed on glass substrates by spray pyrolysis technique. Structural, optical and electrical properties were optimized and improved by varying the film thickness and the annealing temperature. The film thickness was estimated by using the weight difference method. X-ray diffraction patterns showed that all the films were polycrystalline with monoclinic structure and with two main peaks. (1̅11) and (111). The best crystallinity was obtained for a thickness equal to 2270 nm. Optical analysis revealed that CuO thin films have a low transmittance in the visible range indicating a high absorbance. The optical band gap value for CuO thin films decreased from 1.63 eV to 1.52 eV as the thickness increases from 180 nm to 2900 nm. The electrical response of these films was studied using impedance spectroscopy technique. The use of an equivalent circuit allowed us to conclude that films elaborated with an optimum thickness of 2270 nm have the best conductivity. To empathize this conclusion, Hall Effect measurements were performed and exhibited that CuO thin layers with this optimum thickness have the lowest resistivity of 8.51 Ω cm. Since this resistivity is not low enough, we applied annealing in air at different temperatures. Electrical properties were studied by impedance spectroscopy and Hall effect showed that CuO thin films with 2270 nm thickness and annealed at 450 °C for 1 h in air, have the best electrical conductivity with a lowest resistivity of 0.1 Ω cm. Graphical abstract: Image 1 Highlights: CuO thin films were synthesized by spray pyrolysis technique. The optical band gap value for CuO thin films decreased from 1.63 eV to 1.52 eV as the thickness increases from 180 nm to 2900 nm. That CuO thin films with 2270 nm thickness and annealed at 450 °C for 1 h in air, have the best electrical conductivity with a lowest resistivity of 0.1 Ω cm.